'Center of mass movement in cross-country skiing' - A waste of energy or the prerequisite to ski fast - Stöggl, T.; Müller, E.; Holmberg, H. C. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The movement of the center of mass (COM) in cross-country skiing (XCS) has been described by several authors (e.g. Norman & Komi, 1987); however, only at moderate skiing speeds and no relation to performance was analyzed. In sprint running low vertical oscillation of the COM was shown to be beneficial (Anderson, 1996). Whether or not Variation of the COM in horizontal and vertical direction in XCS is related to maximal speed (Vmax) is still open to question.